Ritual Art: a Key to the Ancient Egyptian Book of the Dead - Podemann Sørensen, Jørgen (Scripta Instituti Donneriani Aboensis, 1996)
The Bambara sculpture is a ritual object, in fact one of the dramatis personae of a ritual drama. The Civara, as it is called, is carried on the head during the ritual dance as a token of the presence of the mythical antilope which brought agriculture to the Bambara. Besides the male Civara there is also a female one, and in their dance, the two of them dramatize the fertilizing interaction of sun and soil. Without further exploring Bambara ritual, we may notice that a piece of pictorial art is here an integral part of a ritual. It is a mask, carried during the dance and designating its bearer as the mythical antilope. Also belonging to a ritual are the space and the surroundings in which it is carried out. It is well known how ritual places and temple rooms are often structured and decorated to make out the background and the framework of ritual acts. The place of ritual may be designed as an imago mundi, or it may be chosen or named according to mythical prototypes. Temple rooms may be decorated with mythological and cosmological motifs to identify the ritual acts that take place in them as mythical deeds and cosmologically significant events, exactly as the civara-mask identifies the ritual dance in its mythological and cosmological significance.